Business Cycle Volatility in Germany - Claudia M. Buch; Joerg Doepke; Christian Pierdzioch (Kiel Institute for World Economics (IfW), 2002)
Stylized facts suggest that output volatility in OECD countries has declined in recent years. However, the causes and the nature of this decline have so far been analyzed mainly for the United States. In this paper, we analyze whether structural breaks in the dynamics and the volatility of the real output process in Germany can be detected. We report evidence that output volatility has declined in Germany. Yet, this decline in output volatility is not as clear-cut as it is in the case of the United States. In consequence, it is difficult to answer the question whether the decline in output volatility in Germany reflects good economic and monetary policy or merely ?good luck?.
Keywords: G15; E32; F47; F41; F36; 330; Business Cycle; Volatility; Germany; Konjunktur; Volatilität; Schätzung; Deutschland